2016
DOI: 10.1097/md.0000000000003393
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Radiofrequency Ablation Combined With Ablated Lesion Elimination and Transarterial Chemoembolization Improves the Outcome of Solitary Huge Hepatocellular Carcinomas 10 cm or Larger

Abstract: This study investigated the effectiveness of a new strategy, repeated radiofrequency (RF) ablation combined with ablated lesion elimination following transarterial chemoembolization (TACE)/transarterial embolization (TAE), for solitary huge hepatocellular carcinoma (SHHCC) 10 cm or larger.From July 2008 to October 2015, 39 consecutive patients with SHHCC were screened. Of these, 12 were treated with TACE/TAE and repeated RF ablation (TACE/TAE + RF ablation group) and the remaining 27 patients were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, our results showed that HCC patients who received TACE-RFA on tumor diameters larger than 5 cm and even greater than 10 cm exhibited better OS than those who had only TACE. These are similar to Ke et al ’s clinical findings[ 22 ]. Hence, we should use RFA flexibly in patients with liver cancer after fully evaluating their condition, regardless of tumor size.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results showed that HCC patients who received TACE-RFA on tumor diameters larger than 5 cm and even greater than 10 cm exhibited better OS than those who had only TACE. These are similar to Ke et al ’s clinical findings[ 22 ]. Hence, we should use RFA flexibly in patients with liver cancer after fully evaluating their condition, regardless of tumor size.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical variables included tumor factors and therapeutic alliance. Several reports had pointed out TACE combined with MWA was safe and effective in the treatment of large HCC lesions [30][31][32]. Furthermore, the convenience of using nomogram derived from pretreatment clinical variables to assess prognosis for individual patients with HCC before initiation of treatment may improve patient-physician communication, decision making and selection of patients for prospective clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…( 92 ) also found that enlarging the ablation margin could significantly reduce the risk of tumor recurrence and improve the long-term survival rate. In a previous study, we demonstrated that repeated RFA with an ablation margin and transarterial chemoembolization improved the outcome in patients with large solitary HCCs measuring ≥10 cm ( 93 ). Moreover, our yet to be published current research demonstrates that long-term overall survival is not significantly different between anatomic resection and RFA with an ablation margin ≥1.0 cm in patients with a solitary HCC measuring ≤3 cm.…”
Section: Strategies To Prevent Progression Of Hcc After Rfamentioning
confidence: 98%